Pharmacoeconomic Analysis of Cost Comparison Between Calcium Channel Blocker (CCB) and Angiotensin II Receptor Blocker (ARB) Antihypertensive Drugs in Hospitalized Hypertensive Patients at RSU Royal Prima - Cherryl A.M Simbolon; Razoki; Asyrun Alkhairi Lubis (Jurnal FARMASIMED (JFM), 2026)
Hypertension is a global health problem that contributes substantially to morbidity and mortality, thus requiring therapeutic management that is both clinically effective and economically efficient. In clinical practice, Calcium Channel Blockers (CCB) and Angiotensin II Receptor Blockers (ARB) are commonly used, either as monotherapy or in combination, but they differ in terms of cost and effectiveness. This study aimed to conduct a pharmacoeconomic analysis by comparing the costs and effectiveness of antihypertensive therapy using CCB and ARB in hospitalized hypertensive patients at RSU Royal Prima Medan. The study employed a retrospective design with a pharmacoeconomic analysis approach. Data were obtained from the medical records of hospitalized hypertensive patients during the period October–December 2024 using a total sampling technique, resulting in 52 patients who received CCB therapy, ARB therapy, or a combination of CCB + ARB. The analysis included patient characteristics, treatment costs, therapeutic effectiveness based on achievement of target blood pressure <140/90 mmHg, and calculation of the Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER). The results showed that the combination therapy of CCB + ARB had the highest total treatment cost, while the lowest average cost per patient was found in the ARB monotherapy group. In terms of effectiveness, CCB monotherapy demonstrated the highest effectiveness (75.0%). ACER analysis indicated that CCB monotherapy was the most cost-effective therapy, and ICER analysis confirmed that CCB dominated both ARB and the CCB + ARB combination. In conclusion, CCB monotherapy is the most cost-effective antihypertensive treatment option for hospitalized hypertensive patients at RSU Royal Prima Medan.